Sexual function in women with pelvic floor disorders - Rogers, Rebecca G. (Canadian Urological Association Journal, 2013)
Pelvic floor disorders (PFDs) can impact sexual function. This summary provides an overview of the impact of stress urinary incontinence and pelvic organ prolapse and their treatments on sexual function. In general, interventions that successfully address PFDs will generally improve sexual function as well. However, there are patients whose sexual function will remain unchanged despite treatment, and a small but significant minority who will report worsened sexual function following treatment for their pelvic floor dysfunction.